The Position and Function of the Election Supervisory Agency in the Indonesian Constitutional System: A Case Study of the Dispute Over the 2024 Presidential and Vice Presidential General Elections - Sebastian, William Markus; Tjiptabudy, Jantje; Bakarbessy, Andress Deny (Postgraduate Program in Law, Universitas Pattimura, 2026)
Introduction: Elections are vital in democracy, enabling people to choose leaders. In Indonesia, the General Election Supervisory Body (Bawaslu) ensures transparency, integrity, and fairness in every election stage, nationally and regionally. Its role is crucial for overseeing the 2024 Presidential and Vice-Presidential Elections to guarantee free and fair processes.Purposes of the Research: This study aims to analyze Bawaslu's legal standing within Indonesia's constitutional framework and evaluate the supervisory mechanisms implemented by Bawaslu for the 2024 Presidential and Vice-Presidential Elections.Methods of the Research: The study adopts a normative juridical approach by examining various relevant laws and regulations, particularly Law Number 7 of 2017 on Elections. Additionally, a case study approach is utilized to gain a deeper understanding of the challenges faced by Bawaslu in performing its oversight duties.Results Main Findings of the Research: This study finds that Bawaslu's legal standing as an independent election oversight institution is clearly established in Law Number 7 of 2017. Despite its authority to address violations, challenges like evidence sufficiency and bias allegations persist, often escalating cases to the Constitutional Court. Reforming oversight mechanisms is essential to strengthen accountability and public trust in elections.